Challenges of the Scientific Investigation into Abkhazia and its Surrounding Territories: A Critical Analysis Perspective - Gvantseladze, Teimuraz (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The present work provides a critical evaluation of the hypothesis put forward in the scientific study of Abkhazia, which has distorted the historical narrative of Abkhazia and its neighboring Georgian provinces, thereby fueling separatism. In the examination of Abkhazia’s history, both Georgian and Abkhaz scholars employ linguistic material as either an additional or fundamental source. However, regrettably, they often neglect the fact that linguistic analysis requires specific methodologies, and drawing false and sometimes unscientific conclusions based solely on superficial analysis, while disregarding recommended procedures, is not only unacceptable but also detrimental. Therefore, before utilizing the scholarly heritage of previous generations, it is imperative to ascertain the accuracy and validity of these ideas through linguistic methodology. This study delves into the viewpoints of esteemed scholars such as N. Marr, I. Javakhishvili, and S. Janashia regarding the etymology of certain lexical units documented in Western Georgia from the perspective of modern linguistics. We challenge the Abkhazian and Circassian origins attributed to toponyms like Tskhumi, Pasisi, Chibati, Ancha, Kutatisi, Boboqvati, as well as hydronyms such as Gubazouli and Supsa, and the masculine name and surname Gubazi. The specific hypothesis subjected to our critical analysis lacks a sound methodological foundation and requires linguistic substantiation. It is also evident that the claims made by Abkhaz separatists regarding the preexistence of various parts of Western Georgia (including Abkhazia, Samegrelo, Imereti, Racha, Guria, and Adjara) before the arrival of Georgians are unfounded.